Long-distance reflexives - Cole, Peter, 1941-; Hermon, Gabriella; Huang, Cheng-Teh James (San Diego, CA : Academic Press, 2001)
This new volume serves to focus and clarify the debate surrounding long-distance reflexives by examining the role of syntax, semantics, and pragmatics/discourse in the use of long-distance reflexives in a variety of languages. Graduate students, upper class undergraduates, theoretical linguists, computational linguists, psycholinguists, and linguists at large will find this an important tool. Syntacticians, as well as specialists in language acquisition and processing, will find the volume central to their work. The book is also of great value to those interested in Asian languages, especially Chinese. It will serve as primary reading material for seminars on anaphora. Among its key features, it discusses a broad range of questions about syntactic categories and presents a number of theoretical frameworks.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Grammar, Comparative and general -- Reflexives; Anaphora (Linguistics); Government-binding theory (Linguistics); Grammar, syntax; Language Arts & Disciplines -- Grammar & Punctuation; Medical -- Audiology & Speech Pathology